Analysis of Population, Education Level, Wage Level, and Health Level on Labor Absorption in Bekasi City - Silitonga, Vitri Alfrida; Engka, Daisy S.M.; JSumual, Jacline I. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of economic development is to increase per capita income and long-term public welfare, while bringing about changes in economic structure and income distribution. The goal of economic growth in Indonesia is the welfare of society as a whole. The level of population, education, wages, and health in relation to labor absorption in Bekasi City is the main subject of this study. Quantitative research with secondary time series data from 2008-2023 is the methodology used. Multiple linear regression is the research approach used, and Eviews 12 is used for processing. The regression findings show that, while variables related to health and education levels have a substantial impact on employment, population and salary level variables do not. In Bekasi City, employment is thus affected simultaneously by variables related to population, education, wages, and health.